Study of Design and Implementation of 3D Printing in FRP Shipbuilding - Mustika Ningrum; Fitri Hardiyanti; Heri Supomo (WAVE: Jurnal Ilmiah Teknologi Maritim, 2025)
3D Printing is becoming a more reliable and professional manufacturing method. The benefits of additive manufacturing such as design optimization, weight reduction, and ease of prototyping are factors that speed up the 3D printing process. Although further research on 3D printing is still needed, in some specific applications, 3D printing can be useful. The maritime industry still uses conventional technology in shipbuilding. In addition, shipbuilding has to face very high classification requirements that compel the use of technology that ensures repeatability and high quality. The factor of the length of the process is due to difficulties in the raw materials for shipbuilding. Fiberglass is an alternative basic material for shipbuilding with sufficient material availability, relatively cheap prices, light weight, and more flexibility in catching fish. Fiberglass boats have a longer service life, corrosion resistant, light weight, low production and maintenance costs, and effectively increase fishing. The difficulty of the conventional method of hand lay-up and vacuum infusion in the construction of fiberglass boats is due to the difficulty of determining the composition of the material, as well as the emergence of air bubbles which causes a decrease in the strength of the ship. So the chopper gun method is an efficient method. This research provides information about current R&D in the field of 3D Printing application in shipbuilding, especially ships made of Fiberglass, possible benefits, methods, materials, and opportunities.